Pengaruh Variasi Bahan Pengikat Terhadap Kekuatan Cetakan Pasir, Permeabilitas, Fluiditas, Kekerasan Logam dan Kualitas Hasil Pengecoran Logam Paduan Al-Si Dengan Metode Gravity Casting - Dian Adi Putra; Siswanto Siswanto; Poppy Puspitasari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2021)
This research was conducted to investigate the effect of binder variation including bentonit, lapindo mud, and portland cement on the silica molding sand strength, permeability, fluidity, metal hardness and the quality of Al-Si alloy casting by using gravity casting method. The experimental design was used on this research and analyzed by using descriptive data analysis. The result showed molding sand containing 15% lapindo mud binder had the highest wet compressive strength (8,73 N/cm2). The molding sand containing 15% portland cement binder had the highest dry compressive strength (>32 N/cm2). The highest wet tensile strength was resulted by the molding sand containing 15% bentonit binder (3,33 N/cm2), while the highest dry tensile strength was resulted by the molding sand containing 15% portland cement binder (18,60 N/cm2). The highest wet shear strength was resulted by the molding sand containing 15% portland cement binder (0,57 N/cm2), while the highest dry shear strength was resulted by the molding sand containing 15% portland cement binder (1,03 N/cm2). The molding sand containing 15% bentonit binder had the finest permeability (210 mm/minute). In the real practical application, the molding sand containing 15% portland cement binder was unable to result an appropriate molding strength when manually compressed in cope and drag (casting flask), thus it was unable to use as metal pouring media. The molding sand containing 15% lapindo mud binder had the finest fluidity but it had the lowest hardness (120,30 HV). The molding sand containing 15% bentonit binder resulted the best Al-Si alloy casting quality and the highest hardness (129,60 HV).